The TAR decoder-a bandpass Viterbi/FFT decoder for convolutional encoded spread-spectrum signals - Tomlinson, M.; Abu-Rgheff, M.N.A. (IEEE transactions on communications, 1996)
A new form of bandpass convolutional decoder termed the TAR decoder is presented. The decoder has as its basis the classic Viterbi algorithm, but uses a fast Fourier transform (FFT) in order to cope with a frequency offset, phase rotating, received signal. The TAR decoder also uses a two-dimensional (2-D) despread signal history array in addition to the usual path history registers. The advantage of the TAR decoder is that the decoder does not need to be preceded by a modem and is not subject to the problems of cycle slips. It can operate at negative input signal-to-noise ratio (SNR) values and is well suited to the decoding of low rate convolutional codes as may be used in code-division multiple-access (CDMA) systems. Symbol timing recovery is still required but this is straightforward in practical cases down to /spl sime/-15 dB SNR.